2018
DOI: 10.1159/000488465
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Follow-Up Results of Transobturator Tape Procedure with and without Concomitant Vaginal Surgery

Abstract: Objective: This study aims to evaluate the subjective and objective outcomes of the transobturator tape (TOT) procedure performed to treat stress urinary incontinence and to determine the efficacy and safety of the TOT procedure when used along with vaginal surgery. Methods: This is a prospective review of 24 women who had the TOT procedure done only due to stress incontinence; 22 women who underwent concomitant TOT and pelvic floor repair; and 20 women who received concurrent TOT, transvaginal hysterectomy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Most published studies show equal efficacy of TOT used as a single procedure or combined with prolapse surgery [18][19][20][21]. Only the results of 2 studies revealed a better outcome for sling performed concomitantly with prolapse surgery [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies show equal efficacy of TOT used as a single procedure or combined with prolapse surgery [18][19][20][21]. Only the results of 2 studies revealed a better outcome for sling performed concomitantly with prolapse surgery [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis, <40% of surgeons use validated questionnaires to assess urinary symptoms to evaluate the effectiveness of SUI surgeries [17]. After female MUS, publications of VD most commonly consider PVR as the end point of the studies [8, 12, 18, 19]. It is non-invasive, measurable by ultrasound, reproducible, comparable, traceable, and a key indicator for further therapeutic decisions.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, and because subjective complaints are difficult to define, measure, compare, or reproduce, the primary end point of the study was considered to be objectively measurable PVR >50 mL. Since there is no clear definition of “significant PVR,” in general, PVR above 100 mL is interpreted as such [8, 12, 18, 19]. Other authors used the 50-mL limit because, among their patients with postoperative VD, the ratio of PVR 50–100 mL were higher than those PVR above 100 mL (7.1% vs. 2.6%) [24].…”
Section: Discussionmentioning
confidence: 99%